An iterative detection technique for DS-CDMA signals with strong nonlinear distortion effects - Dinis, Rui (2013)
Whenever a DS-CDMA signal (direct sequence code division multiple access) is the sum of several components associated to different spreading codes (e.g., the DS-CDMA signal to be transmitted by the BS (Base Station) in the downlink, or any multicode DS- CDMA signal), it has high envelope fluctuations, and a high PMEPR (Peak-to-Mean Envelope Power Ratio) setting strong linearity requirements for the power amplifiers. For this reason, it is desirable to reduce the envelope fluctuations of the transmitted signals. A promising class of nonlinear signal processing schemes, combining a nonlinear operation in the time- domain with a linear, frequency-domain filtering operation, was recently proposed for reducing the envelope fluctuations (and, inherently, the PMEPR) of DS-CDMA signals, while maintaining the spectral occupation of the corresponding conventional DS-CDMA signals. However, the performance degradation due to the nonlinear distortion effects on the transmitted signals can be relatively high, especially when a low PMEPR is intended. This can be especially serious if different powers are assigned to different spreading codes. To avoid significant performance degradation in these situations, we consider improved receiver where there is an iterative estimation and cancelation of nonlinear distortion effects. Our performance results show that the proposed receiver allows significant performance improvements after just a few iterations, even when we have strong nonlinear distortion effects.